Análisis de los sistemas de costos de producción aplicado a la empresa MELANIC ubicada en el cantón Salcedo, período 2018. - Bustos Villagómez, Karla Estefanny (2020)
There are many companies that need to know the cost of their products offered, with the purpose of making the best decisions, however, they only know an approximation of it, since they have a poor or non-existent cost system, therefore it is of utmost importance for companies, have a system to correct the ignorance of the elements of cost and obtain the real cost of production, it is for this reason that this research project has identified that the main problem in the MELANIC company is the inefficient management of the costs that allow to know the real cost of production, as a result an adequate price cannot be established for the product, the objective is to analyze the methodology of the production cost systems through a simulation, so that the costs are established of production. For the development of the project, the qualitative and quantitative approach, bibliographic or documentary research and field research were used, such as observation and interview research techniques, applied to the owner of the company. With the analysis it was obtained that said company does not have any cost system that allows it to control and record the expenses and costs incurred in the elaboration of the product; In addition, through the simulation of the two cost systems, it was observed that each one has different methodology and objectives to determine the three cost elements. Through the comparison, it is concluded that the process cost system is the most suitable for the business, adjusting to its requirements, being the one that produces the lowest cost in the production of ice cream that allows the business to generate profitability.